The Effect of Fracture Type on Restoration of Radiographic Parameters and Early Loss of Reduction in Surgical Treated Distal Radius Fractures - Varun Sambhariya; Tyler Roberts; Colin Ly; Alison Ho; William F. Pientka (Trauma Care, 2023)
Purpose: Early loss of reduction remains a challenging complication in distal radius fracture management. There are limited data on factors that correlate with early loss of reduction. The Arbeitsgemeinschaft für Osteosynthesefragen (AO) classification has become a popular way of evaluating complex fracture patterns. This study aims to determine the impact of fracture pattern, as determined by the AO classification, on restoration of intraoperative parameters, early loss of reduction, and time to fracture union in operatively treated distal radius fractures. Methods: Following IRB approval, adult patients with surgically treated acute distal radius fractures at a single level I institution were identified. Retrospective chart and radiographic review were used to obtain AO classification, postoperative radiographic parameters, early loss of reduction, time to fracture union, as well as any complications. Results: 422 patients with operatively treated distal radius fractures were included in this study. Across fracture patterns, there were no significant differences in restoration of radial height or inclination. Higher severity fracture classifications had decreased restoration of volar tilt. Overall, simple fractures (A2, C1) and partial articular fractures (B1, B2, B3) had higher rates of satisfactory alignment restoration compared to comminuted fractures (A3, C2, C3). Although there were differences in restoration of radiographic parameters, fracture type did not correlate with loss of reduction within 30 days. C type fractures correlated with increased weeks to radiographic healing. Conclusions: This study establishes that distal radius fracture pattern, as determined by the AO classification, has a significant impact on intraoperative restoration of parameters but does not correlate with early loss of reduction. Furthermore, more difficult fracture patterns may have a longer time to fracture union, but fracture type does not appear to have an effect on postoperative complications.